2017
DOI: 10.1002/alr.21948
|View full text |Cite
|
Sign up to set email alerts
|

Acute impact of continuous positive airway pressure on nasal patency

Abstract: Acute exposure to positive pressure via CPAP is associated with subjective and objective reductions in nasal patency. In individuals with allergic nasal symptoms, deterioration is even more severe than in patients without these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…A small study by Iriz et al () showed a decrease in minimal cross‐section area after 1 month with PAP, while after 3 months on PAP the area was back to baseline values. Another study by Balsalobre et al () found more subjective and objective (AR) nasal obstruction immediately after 2 hr of PAP use in non‐OSA patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A small study by Iriz et al () showed a decrease in minimal cross‐section area after 1 month with PAP, while after 3 months on PAP the area was back to baseline values. Another study by Balsalobre et al () found more subjective and objective (AR) nasal obstruction immediately after 2 hr of PAP use in non‐OSA patients.…”
Section: Discussionmentioning
confidence: 93%
“…When focusing on the anatomical aspects, Iriz et al () demonstrated a decrease in nasal dimensions measured with acoustic rhinometry (AR) after 1 month of PAP use, and a return to baseline values after 3 months of PAP usage. Balsalobre et al () has described immediate subjective and objective nasal blockage after 2 hr of PAP use. To our knowledge, the long‐term effect of PAP on internal nasal dimensions has not been described, and no large, well‐defined, prospective study has investigated the nose, either objectively or subjectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while most of the studies have revealed an infiltration of neutrophils into inflamed nasal mucous membrane following CPAP treatment of OSAHS patients, 6 not all of the studies have observed the same rhinitis symptoms. 5 , 6 , 13 , 14 These differences may be due to the methodologies used. For the prospective studies that have been conducted, these have rarely extended over more than one year due to the difficulties associated with long-term follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in individuals with allergic nasal symptoms, said deterioration is more severe than in patients without these symptoms. 9 Thus, it is worth considering that baseline inflammation due to AR could increase or exacerbate the inflammatory effect of high airflow in the nasal cavity as the result of CPAP and lead to greater CPAP intolerance.…”
Section: Introductionmentioning
confidence: 99%